The viability of treated piggery wastewater for reuse in agricultural irrigation - Viviane F Velho; Rodrigo A Mohedano; Paulo Belli Filho; Rejane HR Costa (International Journal of Recycling of Organic Waste in Agriculture)
Background: The swine production is a very important economic matter, occupying prominent position in the worldwide market. However, it appears as the greater impacting activity for the water resources. Researches point a swine manure production of 105.6 million m3 /year in Brazil, which resulted in a piggery wastewater rich in solids, nutrients, heavy metals, and pathogens. Moreover, the water consumption for swine production is approximately 15 L/animal/day in southern Brazil, resulting in an unsustainable water resource demand. Thereby, this study verifies the viability of two parallel stabilization reservoirs as a technology for polishing treated piggery wastewater. This technology has been shown effective in reducing organic matter, nutrients, and pathogens in the treatment of the effluents with low or high organic load rate. The reservoirs can improve effluent quality with minimal energy costs to simple operations. The technique would promote the value of the effluent through its reuse for agricultural irrigation. The study was conducted at a farm in the city of BraÃ§o do Norte, Santa Catarina, in southern Brazil; this region has one of the largest densities of pigs in the world, which causes serious environmental problems. Results: The effluent monitoring program included operation during both cold seasons (period I) and warm seasons (period II). The performance of the reservoirs improved continuously during the cold seasons, with the removal efficiencies of total biochemical oxygen demand (BOD5), total Kjeldahl nitrogen (TKN), and Escherichia coli reaching 52%, 64%, and 99.9%, respectively, with an effluent concentration of 144 mg·Lâ1 for BOD5 and 256 mg·Lâ1 for TKN. During the warm seasons, the BOD5, TKN, and E. coli removal efficiencies increased to 85%, 77%, and 99.9%, respectively, with an effluent concentration of 52 mg·Lâ1 for BOD5 and 136 mg·Lâ1 for TKN, which indicates that seasonal factors greatly influence the removal of these variables. E. coli concentrations were not verified into stabilization reservoirs on both periods. Conclusions: The results of this study confirmed that the stabilization reservoirs are capable experimental units promoting improved quality of the treated effluent. A seasonal influence was evident. The results demonstrated that the effluent was a good alternative for unrestrained irrigation use. The microbiological quality complies with the World Health Organization recommendations. The reuse of this treated effluent can reduce pig manure impacts on the environment and water resources.